International conflict mediation [ new approaches and findings - Bercovitch, Jacob; Gartner, Scott Sigmund , 1963- (Security and conflict management, 2009)
Examines how various empirical approaches to mediation can focus on the effectiveness of different patterns of conflict management, and offers guidelines on the process of international mediation. This book captures changes in the field of international conflict mediation, and includes essays on a variety of aspects of conflict management